Dinamika Tradisi Tari Gubang pada Suku Melayu di Kecamatan Tanjungbalai - Julia Arsyka Abdha; Laila Rohani (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This research delves into the Gubang dance, a traditional art form originating from Tanjungbalai Asahan, North Sumatra. It centers on investigating its origins, functions, development, and preservation challenges. The research employs fieldwork and interviews with traditional arts experts to gather reliable data. The findings uncover that the Gubang dance holds profound significance as a symbol of unity and gratitude within Asahan's cultural tapestry. Its graceful, dynamic movements mirror the beauty of Indonesian culture, necessitating preservation efforts. However, the Gubang dance grapples with challenges, notably waning interest among younger generations. In response, the research underscores the imperative of promoting and preserving the Gubang dance. Such initiatives are pivotal to ensure it doesn't fade into obscurity, remaining an integral facet of invaluable cultural heritage. This study validates the importance of traditional dances as regional cultural identifiers and emphasizes the need for concrete actions to safeguard this cultural wealth for continued relevance and vitality.